Reduction in mdx mouse muscle degeneration by low-intensity endurance exercise: a proteomic analysis in quadriceps muscle of exercised compared with sedentary mdx mice. Issue 3 (22nd June 2015) - Fontana, Simona; Schillaci, Odessa; Frinchi, Monica; Giallombardo, Marco; Morici, Giuseppe; Liberto, Valentina Di; Alessandro, Riccardo; De Leo, Giacomo; Perciavalle, Vincenzo; Belluardo, Natale; Mudò, Giuseppa
Abstract : By proteomic analysis we found an up-regulation of four carbonic anhydrase-3 (CA3) isoforms and a down-regulation of superoxide dismutase [Cu-Zn] (SODC) in quadriceps of sedentary X-linked muscular dystrophy (mdx) mice as compared with wild–type (WT) mice and the levels were significantly restored to WT values following low-intensity endurance exercise. Abstract : In our recent study was shown a significant recovery of damaged skeletal muscle of mice with X-linked muscular dystrophy ( mdx ) following low-intensity endurance exercise, probably by reducing the degeneration of dystrophic muscle. Consequently, in the present work, we aimed to identify proteins involved in the observed reduction in degenerating fibres. To this end, we used proteomic analysis to evaluate changes in the protein profile of quadriceps dystrophic muscles of exercised compared with sedentary mdx mice. Four protein spots were found to be significantly changed and were identified as three isoforms of carbonic anhydrase 3 (CA3) and superoxide dismutase [Cu-Zn] (SODC). Protein levels of CA3 isoforms were significantly up-regulated in quadriceps of sedentary mdx mice and were completely restored to wild–type (WT) mice values, both sedentary and exercised, in quadriceps of exercised mdx mice. Protein levels of SODC were down-regulated in quadriceps of sedentary mdx mice and were significantly restored to WT mice values, both sedentary and exercised, in quadriceps of exercised mdx mice. Western blot data were in agreement with those obtained using proteomic analysis and revealed the presence of one more CA3 isoform that was significantly changed. Based on data found in the present study, it seems that low-intensity endurance exercise may in part contribute to reduce cell degeneration process in mdx muscles, by counteracting oxidative stress.